Nuclear genetic diversity of head lice sheds light on human dispersal around the world - Ascunce, Marina Sofia (2023)
The human louse, Pediculus humanus, is an obligate blood-sucking ectoparasite that has coevolved with humans for millennia. Because of the intimate relationship between this parasite and the human host, the study of human lice has the potential to shed light on aspects of the human evolution that are obscured or difficult to interpret using other biological evidence. In this study, we analyzed the genetic variation in 274 human lice from 25 geographic sites around the world by using nuclear microsatellite loci and female-inherited mitochondrial DNA sequences. Nuclear genetic diversity analysis revealed the presence of two distinct genetic clusters I and II, which are subdivided into subclusters: Ia-Ib and IIa-IIb, respectively. Among these samples, we observed the presence of the two most common louse mitochondrial haplogroups: A and B. Both mitochondrial haplotypes were found in nuclear Clusters I and II. Evidence of nuclear admixture was uncommon (33 lice) and was predominately found in the New World potentially mirroring the pattern of very recent host admixture between Native Americans and Europeans. These findings were supported by novel DIYABC-simulations that were built using both host and parasite data to define parameters and models. In addition to providing new evolutionary knowledge about this human parasite, our study could guide the development of new analyses in other host-parasite systems.